IMPLEMENTASI PENGOLAHAN SISTEM PENJUALAN FURNITURE MENGGUNAKAN METODE DESIGN THINKING (STUDI KASUS : FURNITURE JATI SUNGU BANDAR LAMPUNG) - eci astria risti (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2022)
Teak Sungu furniture in the process of processing sales transactions is still manual so that it produces inaccurate and irrelevant information. Staff also have difficulty in making monthly sales reports, because reports are recapitulated based on daily sales transactions, through sales notes, if left continuously it will take up data storage space and time only for notes and sales reports. Manual data processing is also vulnerable to data manipulation, so that the data or sales reports produced are not necessarily reliable. From these problems, the researchers developed a website-based sales information system. The sales information system was developed using the system development method, namely design thinking. A website-based sales information system can help Jati Sungu Furniture Bandar Lampung in recording and managing sales transaction data better than the previous system, so that previously poor quality data becomes accurate and relevant information. the system that has been developed also helps in making monthly sales reports more easily and quickly, the data is also difficult to manipulate because there are user access rights with a login system. the system has also been tested with ISO 25010. The test results of ISO 25010 have a percentage value of 92.9% and are very feasible to be implemented on Teak Sungu Furniture Bandar Lampung